A challenging case of severe sickle cell crisis: a case report on vaso occlusive crisis in sickle cell disease with multi organ failure - Dihingia, Prasanta; Doley, Rima Moni; Borah, Arniban; Phukan, Anwesha; Ilangovan, Karthik; Saha, Akshay (International Journal of Research in Medical Sciences, 2025)
Sickle cell disease involves recurrent hemolysis and vaso occlusive crisis, which occurs mainly due to abnormal Hemoglobin S polymerization and sickling of erythrocytes. These sickled erythrocytes are prone for damage in micro capillaries, escalating into vaso occlusive crisis presenting as acute pain episodes and recurrent hospitalisations. Severe vaso occlusive crisis can precipitate multi organ dysfunction and failure, significantly increasing morbidity and mortality. This report presents a 19-year-old male with known sickle cell disease who developed a severe vaso occlusive crisis complicated by multi organ failure, including acute chest syndrome, renal impairment, and liver dysfunction. The patient presented with generalized joint pain, chest discomfort, dyspnea, and oliguria. Clinical evaluation revealed pallor, mild icterus, hypoxemia, and hemodynamic instability. Investigations demonstrated bilateral pulmonary infiltrates, pleural effusions, and deranged liver and renal function tests. Management included aggressive intravenous hydration, oxygen therapy, blood transfusion, hydroxyurea, broad spectrum antibiotics, anticoagulation, and supportive care. Despite clinical deterioration necessitating intensive care and non-invasive ventilation, the patient responded favourably to multidisciplinary intervention, with gradual resolution of organ dysfunction and return to baseline status. This case underscores the critical importance of early recognition, prompt resuscitation, and comprehensive management in sickle cell disease patients with vaso occlusive crisis and evolving multi organ failure. Timely intervention can be lifesaving and is essential for improving outcomes in high-risk sickle cell disease populations.